Pedogenic Processes and Urban Tree Health in Engineered Urban Soils in Boston, Massachusetts, USA. Issue 4 (July 2018) - Scharenbroch, Bryant C.; Fite, Kelby; Kramer, Eric; Uhlig, Robert
Abstract : ABSTRACT: Trees provide many ecosystem services in the urban environment. For these benefits to be realized, trees must establish and grow to large sizes. Engineered urban soils (EUS) are intended to promote tree health and sometimes also perform other functions such as supporting infrastructure. Substantial amounts of time and money are invested into these soils and trees, yet data on longitudinal soil developmental processes (i.e., pedogenic processes) and tree performance are limited for these systems. In this research, soil development in seven EUS installations in Boston, Massachusetts, was assessed. The EUS studied included sand-based structural soils, rock-based structural soils, and horticultural mixes. The sites spanned a chronosequence of 6 to 45 years since installation and included five different tree species. The data confirm the hypotheses that pedogenic processes are occurring in these soils at different rates and magnitudes. Illuviation of clay, acidification, and a decrease in the mineralization quotient (qM, or respiration divided by soil organic matter) were observed with increasing site age. The data suggest that overall soil quality may be influential on tree health, and no individual soil physical, chemical, or biological property is driving site differences important for trees. Urban vegetation managers should recognize that these are not static systems and the actions to care for these systems should evolve as the soils develop over time.